The Role of Innovative Teaching Methods in Improving Learning Outcomes in Islamic Education Vol 2 no 1 - bayu (Innovative Pedagogy and Education Studies, 2025)
This study aims to analyze the role of innovative teaching methods in improving learning outcomes in Islamic education. Innovative teaching methods, including interactive learning, problem-based learning, and the integration of digital media, are essential in creating engaging and effective learning environments. This research uses a qualitative descriptive approach, with data collected through observations, interviews, and analysis of instructional documents. The results indicate that the application of innovative teaching methods enhances students’ understanding, motivation, and active participation in Islamic education classes. These methods also support the development of cognitive, affective, and psychomotor learning outcomes. Despite challenges such as limited facilities and teachers’ technological skills, innovative teaching methods have a significant positive impact on improving learning outcomes in Islamic education.